Small Groups and First-Generation College Goers: An Intervention with African American High School Seniors. Issue 1 (2nd January 2020) - Havlik, Stacey; Malott, Krista; Diaz Davila, Jose; Stanislaus, Denzell; Stiglianese, Sarah
ABSTRACT: This article describes an eight-session psychoeducational small-group intervention with two groups of African-American youth in an urban, east coast high school setting. Sessions were designed to enhance the self-efficacy and outcomes expectations related to attending college for first-generation college goers in the twelfth grade. The group session topics are described, and outcomes are assessed. Facilitator challenges unique to the group setting are included.